Iron Redox Speciation Analysis Using Capillary Electrophoresis Coupled to Inductively Coupled Plasma Mass Spectrometry (CE-ICP-MS) - Michalke, Bernhard; Willkommen, Desiree; Venkataramani, Vivek (Frontiers in Chemistry, 2019)
Neuronal iron dyshomeostasis occurs in multiple neurodegenerative diseases. Changes in the Fe(II)/Fe(III) ratio towards Fe(II) is closely related to oxidative stress, lipidperoxdiation and represents a hallmark feature of ferroptosis. In particular for body fluids, like cerebrospinal fluid (CSF), reliable quantitative methods for Fe(II)/(III) redox-speciation analysis are needed to better assess the risk of Fe(II)-mediated damage in brain tissue. Currently in the field of metallomics, the most direct method to analyze both iron species is via LC-ICP-MS. However, this Fe(II)/(III) speciation analysis method suffers from several limitations. We here describe a unique method using capillary electrophoresis (CE)-ICP-MS for quantitative Fe(II)/(III) speciation analysis that can be applied for cell lysates and biofluid samples. Compared to LC, CE offers various advantages: 1.) Capillaries have no stationary phase and do not depend on batch identity of stationary phases; 2.) Replacement of aged or blocked capillaries is quick with no performance change; 3.) Purge steps are effective and short; 4.) Short sample analysis time. The final method employed 20 mM HCl as background electrolyte and a separation voltage of +25kV. In contrary to the LC-method, no complexation of Fe-species with pyridine dicarboxylic acid (PDCA) was applied, since it hampered separation. Peak shapes and concentration detection limits were improved by combined conductivity-pH-stacking achieving 3 µg/L detection limit (3σ) at 13 nL injection volume. Calibrations from LOD – 150µg/L were linear (r²(Fe(II)=0.9999, r²(Fe(III)=0.9951). At higher concentrations Fe(II) curve flattened significantly. Measurement precision was 3.5% (Fe(II) at 62µg/L) or 2.2% (Fe(III) at 112µg/L) and migration time precision was 2% for Fe(III) and 3% for Fe(II), each determined in 1:2 diluted lysates of human neuroblastoma cells. Concentration determination accuracy was checked by parallel measurements of SH-SY5Y cell lysates with validated LC-ICP-MS method and by recovery experiments after standard addition. Accuracy (n=6) was 97.6 ± 3.7% Fe(III) and 105 ± 6.6 %Fe(II). Recovery ((a) +33µg/L or (b) +500µg/L, addition per species) was (a): 97.2±13% (Fe(II)), 108±15% (Fe(III)), 102.5±7% (sum of species), and (b) 99±4% (Fe(II)), 101±6% (Fe(III)), 100±5% (sum of species). Migration time shifts in CSF samples were due to high salinity, but both Fe-species were identified by standard addition.